Pengaruh Employer Branding dan Stres Kerja terhadap Turnover Intention pada Pekerja Generasi Z : (Studi Kasus: Wedding Organizer di Kota Samarinda) - Zahratul Ula; Asmadhini Handayani Rahmah (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the impact of Employer Branding and work-related stress on Turnover Intention among Generation Z workers, with a case study in the Wedding Organizer industry in Samarinda City. Employer Branding, as an effort by companies to create a positive image in the eyes of employees and potential employees, as well as work-related stress arising from workload, is expected to have a significant influence on employees’ intention to leave their jobs. The data collection method used in this study is through the distribution of questionnaires via Google Forms, which were distributed to Generation Z workers in 5 Wedding Organizers in Samarinda City. The collected data were then analyzed using multiple linear regression to examine the relationship between these variables. The results of this study are expected to provide insights into the factors influencing Turnover Intention among Generation Z workers and offer recommendations for companies to pay more attention to the mental well-being of their employees. With more focus on managing work-related stress and strengthening Employer Branding, companies are expected to build better relationships with Generation Z workers, thereby reducing Turnover Intention and enhancing their well-being in the workplace.